Factors associated with mobile health information seeking among Singaporean women - Chang, Leanne; Chiuan Yen, Ching; Xue, Lishan; Choo Tai, Bee; Chuan Chan, Hock; Been-Lirn Duh, Henry; Choolani, Mahesh (Taylor & Francis, 2017)
This study examined effects of age and social psychological factors on women’s willingness to be mobile health information seekers. A national survey of 1,878 Singaporean women was conducted to obtain information on women’s mobile phone usage, experiences of health information seeking, and appraisals of using mobile phones to seek health information. Results showed that young, middle-aged, and older women exhibited distinct mobile phone usage behaviors, health information-seeking patterns, and assessments of mobile health information seeking. Factors that accounted for their mobile information-seeking intention also varied. Data reported in this study provide insights into mobile health interventions in the future.